When diabetes defies classification: A diagnostic crossroads betweenidiopathic type 1 diabetes and emerging type 5 diabetes - Singh, Avi; Laraib, Mohd; Sharma, Deepak; Srivastava, Saurabh (Indian Journal of Case Reports, 2026)
Atypical forms of diabetes increasingly challenge conventional classification systems, particularly in young leanindividuals presenting with insulin deficiency but lacking autoimmune markers. We report the case of a 22-year-old Indian male with poorly controlled diabetes diagnosed at 17 years of age who presented with fever, generalizedweakness, burning micturition, hypotension, severe metabolic acidosis (arterial pH 6.9), ketonuria, and anemia.Immunological evaluation, including glutamic acid decarboxylase, insulin autoantibodies, insulinoma-associatedantigen-2, zinc transporter 8, and islet cell antibodies, was negative. The patient was managed with intravenous fluids, insulin infusion, electrolyte correction, nutritional support, and antibiotics with gradual clinical improvement. The coexistence of profound insulin deficiency, ketosis, lean body habitus, and probable chronic undernutrition created a diagnostic dilemma between idiopathic type 1 diabetes (type 1B diabetes) and malnutrition-related diabetes mellitus, recently re-emphasized as type 5 diabetes. This report highlights the evolving spectrum of atypical diabetes phenotypes, the limitations of current classification systems, and the importance of recognizing malnutrition-associated diabetes in resource-limited settings.